Relief and Recurrence of Congestion During and After Hospitalization for Acute Heart Failure. (July 2015) - Lala, Anuradha; McNulty, Steven E.; Mentz, Robert J.; Dunlay, Shannon M.; Vader, Justin M.; AbouEzzeddine, Omar F.; DeVore, Adam D.; Khazanie, Prateeti; Redfield, Margaret M.; Goldsmith, Steven R.; Bart, Bradley A.; Anstrom, Kevin J.; et al.
<x xml:space="preserve">Abstract</x> Background— Congestion is the most frequent cause for hospitalization in acute decompensated heart failure. Although decongestion is a major goal of acute therapy, it is unclear how the clinical components of congestion (eg, peripheral edema, orthopnea) contribute to outcomes after discharge or how well decongestion is maintained. Methods and Results— A post hoc analysis was performed of 496 patients enrolled in the Diuretic Optimization Strategy Evaluation in Acute Decompensated Heart Failure (DOSE-AHF) and Cardiorenal Rescue Study in Acute Decompensated Heart Failure (CARRESS-HF) trials during hospitalization with acute decompensated heart failure and clinical congestion. A simple orthodema congestion score was generated based on symptoms of orthopnea (≥2 pillows=2 points, <2 pillows=0 points) and peripheral edema (trace=0 points, moderate=1 point, severe=2 points) at baseline, discharge, and 60-day follow-up. Orthodema scores were classified as absent (score of 0), low-grade (score of 1–2), and high-grade (score of 3–4), and the association with death, rehospitalization, or unscheduled medical visits through 60 days was assessed. At baseline, 65% of patients had high-grade orthodema and 35% had low-grade orthodema. At discharge, 52% patients were free from orthodema at discharge (score=0) and these patients had lower 60-day rates of death, rehospitalization, or unscheduled visits (50%) compared with those with low-grade or high-grade orthodema (52% and 68%, respectively; P=0.038). Of the patients without orthodema at discharge, 27% relapsed to low-grade orthodema and 38% to high-grade orthodema at 60-day follow-up. Conclusions— Increased severity of congestion by a simple orthodema assessment is associated with increased morbidity and mortality. Despite intent to relieve congestion, current therapy often fails to relieve orthodema during hospitalization or to prevent recurrence after discharge. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifiers: NCT00608491, NCT00577135.